Topological surface states of semimetal TaSb2 - Lee, Ji-Eun; Liu, Yu; Hwang, Jinwoong; Hwang, Choongyu; Petrovic, Cedomir; Park, Se Young; Ryu, Hyejin; Mo, Sung-Kwan (Springer | Korea Nano Technology Research Society, 2024)
Topological surface states, protected by the global symmetry of the materials, are the keys to understanding various novel electrical, magnetic, and optical properties. TaSb2 is a newly discovered topological material with unique transport phenomena, including negative magnetoresistance and resistivity plateau, whose microscopic understanding is yet to be reached. In this study, we investigate the electronic band structure of TaSb2 using angle-resolved photoemission spectroscopy and density functional theory. Our analyses reveal distinct bulk and surface states in TaSb2, providing direct evidence of its topological nature. Notably, surface states predominate the electronic contribution near the Fermi level, while bulk bands are mostly located at higher binding energies. Our study underlines the importance of systematic investigations into the electronic structures of topological materials, offering insights into their fundamental properties and potential applications in future technologies.